IMPLEMENTING CONTEXTUAL BIOLOGY GAME LEARNING (CBGL) IN DIGITAL ERA WITH PTERODOVELA IN SMARTPHONE TO IMPROVING SENIOR HIGH SCHOOL STUDENT’S ABILITIES IN LEARNING DIVERSITY OF BRYOPHYTA AND PTERODOPHYTA IN INDONESIA - Setiawan, Heru; Alimi, Muhammad Syukron; Alimah, Siti; Kurniawan, Firman Heru; Zahro, Royna Nafisatuz (PEOPLE: International Journal of Social Sciences, 2015)
The aim of this study are (1) Developing Pterodovela Digital media the diversity of bryophyta and pterodophyta for senior high school students (2) to analyze the feasibility of Pterodovela as learning media. (3) determine the effectivity of contextual biology games learning (CBGL) using Pterodovela to improve student’s achievement and students activity. Methods: This research combines between the educational research and development and experimental research. R&D consists of ten steps: (1) research and information collecting, (2) planning, (3) develop a preliminary form of product, (4) preliminary field testing, (5) main product revision, (6) main field testing. (7) operational product revision, (8) operational field testing, (9) final product revision. (10) implementation. Field testing conducted at 2 senior high schools in Indonesia as many as 96 students. Experimental research design that used was"Randomized Control group pretest-posttest design. Methods of data analysis using percentages description and statistical test with t-test. Conclution: Digital pterodovela very feasible to use in contextual biology game learning (CGBL), received positive response from students and teachers, and effective to improve student’s achievement and learning activities in biology. T-test results of student’s achievement t count = 3.531> t table = 1.645 and learning activities is t=2.25 > t table = 1.645.